Applications of platelet and leukocyte rich fibrin in Dentistry (Research, Society and Development, 2022)
Over the years there was a need to use materials that would provide the production of autologous bioactive surgical additives with the function of establishing hemostasis, controlling the inflammation process and accelerating the healing process, this search developed L-PRF, the second generation of platelet aggregates consisting of a polymerized fibrin matrix, a tetramolecular structure that incorporates platelets, leukocytes, cytokines, growth factors and circulating stem cells, has been used in dentistry in oral surgery, endodontics and periodontics to accelerate the physiological phenomenon of healing, decreasing morbidity in tissue reconstruction procedures. The objective of the research is to highlight the importance and deepen the knowledge about the applicability of L-PRF in dental procedures. This work refers to a descriptive narrative literature review, through a qualitative approach, it was sought to deepen the knowledge on the subject using a bibliographic survey in the Elsevier, Google Scholar and PubMed databases. Thirty articles were selected to support this research, describing how to obtain L-PRF and highlighting the benefits of using it in dental procedures. Platelets have mitogenic, chemotactic and pro-angiogenic properties, promoting and modulating the cellular processes involved in tissue healing. L-PRF makes it possible to reduce postoperative edema and pain. Therefore, its use has shown numerous advantages, due to its various properties: easy to obtain, low cost, good initial tissue healing, it provides a framework for bone formation, reduces inflammation, antibacterial and anti-hemorrhagic effects and the low risks of use that should encourage more dentists to adopt this technology.